2017
DOI: 10.3389/fcvm.2017.00059
|View full text |Cite
|
Sign up to set email alerts
|

Complete Resolution of a Large Bicuspid Aortic Valve Thrombus with Anticoagulation in Primary Antiphospholipid Syndrome

Abstract: Native aortic valve thrombosis in primary antiphospholipid syndrome (APLS) is a rare entity. We describe a 38-year-old man who presented with neurological symptoms and a cardiac murmur. Transthoracic echocardiography detected a large bicuspid aortic valve thrombus. Laboratory evaluation showed the presence of antiphospholipid antibodies. Anticoagulation was started, and serial echocardiographic studies showed complete resolution of the aortic valve vegetation after 4 months. The patient improved clinically and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The estimated prevalence of NBTE ranges from 0.3% to 9.3% (2). In patients with APLS, as many as one-third develop cardiac valve disease (3,4). The case reported here represents a rare occurrence of near resolution of NBTE and improvement in mitral valve regurgitation with warfarin therapy, obviating the need for surgical intervention.…”
Section: Giant Thrombus Occupying the Right Cardiac Chambers In A Canmentioning
confidence: 83%
“…The estimated prevalence of NBTE ranges from 0.3% to 9.3% (2). In patients with APLS, as many as one-third develop cardiac valve disease (3,4). The case reported here represents a rare occurrence of near resolution of NBTE and improvement in mitral valve regurgitation with warfarin therapy, obviating the need for surgical intervention.…”
Section: Giant Thrombus Occupying the Right Cardiac Chambers In A Canmentioning
confidence: 83%
“…Anticoagulation therapy has been used for native aortic valve thrombosis in primary antiphospholipid syndrome, and echocardiography showed complete resolution of the aortic valve vegetation after a few months; the patient improved clinically and had no lingering symptoms. [10] It has been suggested that vegetations in antiphospholipid syndrome can be treated successfully with anticoagulation treatment, regardless of their size. [10] The epidemiological practices indicated that in recent years, the incidence of IE has increased, especially in elderly individuals and hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…[10] It has been suggested that vegetations in antiphospholipid syndrome can be treated successfully with anticoagulation treatment, regardless of their size. [10] The epidemiological practices indicated that in recent years, the incidence of IE has increased, especially in elderly individuals and hospitalized patients. [11,12] In our case, we think that after the patient was suspected to have multi-organ cardiac embolism, early and integrally repeated echocardiography should have been performed as well as risk factor screening; then after weighing the advantage and disadvantage, anticoagulation therapy should have been considered earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The same has been the case for isolated tricuspid valve NBTE associated with APS [ 8 ]. A literature review revealed only scarce reported cases of NBTE presenting as large vegetations in male patients with APS, and those found were restricted to the aortic valve, which is a more common site of NBTE involvement [ 10 ]. We found no published studies addressing gender differences in the prevalence of APS with NBTE.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient was not a candidate for continued medical management due to the severity of his heart failure, as well as an observed lability on warfarin which made it difficult to maintain INR at a therapeutic value. However, recent case reports have shown complete resolution of an aortic valve thrombus with warfarin [ 10 ], as well as resolution of TV NBTE in a patient managed with vitamin K antagonists-hydroxychloroquine (VKA-HCQ) [ 11 ]. Clinical trials are still necessary to further evaluate said treatment options and develop more robust therapies for NBTE in patients with APS.…”
Section: Discussionmentioning
confidence: 99%